Pan-primate studies of age and sex - Steve Horvath; Amin Haghani; Joseph A. Zoller; Ake T. Lu; Jason Ernst; Matteo Pellegrini; Anna J. Jasinska; Julie A. Mattison; Adam B. Salmon; Ken Raj; Markus Horvath; Kimberly C. Paul; et al. (GeroScience, 2023)
Age and sex have a profound effect on cytosine methylation levels in humans and many other species. Here we analyzed DNA methylation profiles of 2400 tissues derived from 37 primate species including 11 haplorhine species (baboons, marmosets, vervets, rhesus macaque, chimpanzees, gorillas, orangutan, humans) and 26 strepsirrhine species (suborders Lemuriformes and Lorisiformes). From these we present here, pan-primate epigenetic clocks which are highly accurate for all primates including humans (age correlation R = 0.98). We also carried out in-depth analysis of baboon DNA methylation profiles and generated five epigenetic clocks for baboons (Olive-yellow baboon hybrid), one of which, the pan-tissue epigenetic clock, was trained on seven tissue types (fetal cerebral cortex, adult cerebral cortex, cerebellum, adipose, heart, liver, and skeletal muscle) with ages ranging from late fetal life to 22.8 years of age. Using the primate data, we characterize the effect of age and sex on individual cytosines in highly conserved regions. We identify 11 sex-related CpGs on autosomes near genes ( POU3F2, CDYL, MYCL, FBXL4, ZC3H10, ZXDC, RRAS, FAM217A, RBM39, GRIA2, UHRF2 ). Low overlap can be observed between age- and sex-related CpGs. Overall, this study advances our understanding of conserved age- and sex-related epigenetic changes in primates, and provides biomarkers of aging for all primates.

Construction and integration of radiation-hybrid and cytogenetic maps of dog Chromosome X - Helen F. Spriggs; Nigel G. Holmes; Matthew Breen; Panos Deloukas; Cordelia F. Langford; Mark T. Ross; Nigel P. Carter; Maria E. Davis; Catherine Knights; Angela Smith; Christine J. Farr; Linda C. McCarthy; et al. (Mammalian Genome, 2003)